The strategies of lean planning at selected construction sites in klang valley, malaysia: A structural equation modeling approach - Ahmed M.E.A.M.; Wong L.S. (Jordan University of Science and Technology, 2023)
Construction industry; Contractors; Human resource management; Lean production; Managers; Construction projects; Design and construction process; Efficient communications; Project organization; Questionnaire data; Strategic modeling; Structural equation modeling; Traditional cultures; Project management